Recuperação de dados da operacionalização de programas governamentais: um estudo do Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) - Moreira, Fábio Mosso [UNESP] (2015)
Research that assess the contributions of Information and Communication Technologies (ICT) for agriculture are recent, both in the issues of use of devices by farmers as in the technological issue of dissemination of information in rural areas. The use of Internet and Web in process that provide government information is growing and brings the possibility for the citizens to monitor actions such as the implementation of public policies. Public policies for agriculture are a major factor in social and economic development of family farming. The importance to provide data about government programs and the need for farmers obtain information about public policies highlights the aims of this study, which is the analysis of data recovery process in the operacionalization of Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) through official websites of public financial institutions involved in implementing of the program. The choice by PRONAF was due to the fact that this is the main program of support for family farming in Brazil, with the largest amount of budgeted financial resources. The methodology used was a qualitative research, being essentially an exploratory-descriptive study, in which was realized a theoretical survey to obtain information to characterize the family farm, conceptualize the theme of public policy, describe the PRONAF and its operating arrangement, and to obtain factors involved in the provision and access to government data on the Web. The colect of data was performed using the method of direct observation on the official websites of public financial institutions to identify information resources containing data queries of the operationalization of PRONAF.The process of data retrieval through the informational resources identified was analyzed having with basis the aims which permeates Data Lifecycle (Preservation, Dissemination,Copyright, Quality, Integration and Privacy). The definition of criteria...